PERFORMANCE SUPERVISION HEALTH SOCIAL SECURITY IMPLEMENTING AGENCY - Muhammad Fitrah Yunus; Fokky Fuad; Sadino Sadino (Indonesian Journal of Law and Policy Studies, 2021)
The study on the supervision of the DPR RI on the performance of BPJS Health is important at least for several reasons: First, the lack of optimal oversight of the DPR's supervisory function has resulted in many violations of the implementation of the laws that have been formed. Second, it is important to find out where the role of the House of Representatives (DPR) is as a state institution that has a supervisory function over the policies that have been taken through Law No. it influences the performance of BPJS. The formulation of the problem in this research is: First, how is the implementation of the supervisory function of the House of Representatives of the Republic of Indonesia on the Social Security Administering Body (BPJS) for Health? Second, What is the obstacles to the implementation of the DPR RI's supervisory function on the performance of the Health Social Security Administering Body (BPJS)? The theoretical framework used in this research is Monitoring Theory. The research method used in this study uses empirical legal research methods. The conclusion of the study: the inability of the DPR-RI in carrying out its function to question various government policies that are deemed less popular or suspected of having no major benefits for the community.